FAKTOR-FAKTOR PEREMPUAN YANG WANITA DENGAN INSIDENSI PREECLAMPSIA DI PUSKESMAS KRESEK DI 2017 - silfia nuzulus sa'idah; solihati solihati; alni sintapea (Jurnal Kesehatan, 2019)
According to research, Mardiani and Neli 2013. It can be seen that most respondents with mother age > 35 years 13 people (76.5%) are at risk of preeclampsia and vice versa that is not as risky as 10 people (11,2), And in Puskesmas Kresek most of the respondents 39 people (72,2%) at risk of preeclampsia and 15 people (27,8) are not at risk. The purpose to find out the factors of pregnant women with the incidence of preeclampsia in Puskesmas Kresek 2017. The research methodology used descriptive correlation research. The population in this study were pregnant women with preeclampsia in Puskesmas Kresek Kabupaten Tangerang April 2017. Samples taken for this study using total sampling that is as much as 54 people pregnant women with preeclampsia. The method of data analysis using Chi Square test. In Puskesmas Kresek the factors of pregnant women with preeclampsia incidence at risky are age (72.2%) were not at risk (27.8%), based on unresponsive parity (72.2%) and at risk (27.8% ), Based on a history of unresponsive pre-eclampsia (79.6%) and at risk (20.4%), based on risk-free obesity (61.1%) (38.9%), based on the results of risky blood pressure (68.5%) are not at risk (31.5%). The conclusion is that there is an age correlation with preeclampsia occurrence in p = 0,01 (p <0,05), no parity relation with preeclampsia occured in p value = 1.71 (p> 0,05), no relation history Preeclampsia with the incidence of preeclampsia was obtained p= 3.22 (p> 0,05), there was an association of obesity with the incidence of preeclampsia obtained p = 0,01 (p <0,05), there was correlation of blood pressure result with incidence of preeclampsia In get value p = 0,00 (p = <0,05).